Anxiety of pregnant women in time of catastrophic events, including COVID-19 pandemic: a systematic review and meta-analysis. (2nd October 2022) - Feduniw, Stepan; Modzelewski, Jan; Kajdy, Anna; Sys, Dorota; Kwiatkowski, Sebastian; Makomaska-Szaroszyk, Elżbieta; Rabijewski, Michał
Abstract: Purpose: In March 2020, daily life was disrupted by the new virus SARS-CoV-2, which causes COVID-19. Pandemic-related prenatal anxiety could lead to depression, a risk factor for adverse pregnancy outcomes and abnormal neonatal development. This study aimed to investigate the impact of anxiety on the mental health of pregnant women exposed to catastrophic events as compared to those without such exposure. Materials and methods: PubMed/MEDLINE, Web of Science, Cochrane Library, Scopus, and EMBASE were searched for relevant studies. This study compared the prevalence of anxiety among pregnant women during a catastrophic event. Results: Fifteen full texts were assessed for inclusion, with 3 included, 10 excluded for not meeting criteria, and 2 excluded for other reasons. The included studies were published before the current COVID-19 pandemic but included the SARS 2003 outbreak. During the current COVID-19 pandemic, 10 further studies were conducted, but they failed to meet the inclusion criteria. A meta-analysis of two studies using STAI revealed that women exposed to a catastrophic event had a higher mean STAI score of 1.82 points (95% CI: 0.47–3.18 points). Conclusion: Women with complications during pregnancy should be assessed for anxiety independently from catastrophic events. During financial crises, environmental or other disasters, special attention should be given to women with low risk, normal pregnancies.